Transapical aortic valve implantation in patients with pre-existing mitral valve prostheses: a case report. Issue 1 (December 2016) - Wachter, Kristina; Ahad, Samir; Rustenbach, Christian; Franke, Ulrich; Baumbach, Hardy
Abstract Background Transcatheter aortic valve implantation (TAVI) has proven to be a valid option for patients with severe aortic stenosis who are at high perioperative risk, particularly in patients with previous cardiac surgery. Several patients with previous mitral valve surgery were reported to have been successfully treated with TAVI. Case presentation Two patients, one with mechanical and one with biological mitral valve prosthesis, presented with symptomatic severe aortic stenosis. After discussion among our multidisciplinary heart team transapical approach and a JenaValve™ prosthesis was used for TAVI. Main reasons were to decrease the perioperative risk, avoid a re-opening of the chest via median sternotomy, and discuss the possible superiority of the JenaValve™ device due to its design. The patients were successfully treated and discharged on the 11th and 14th post-operative day, respectively. Echocardiographic follow up before discharge and up to 2.8 years post-operatively showed excellent results. Conclusions In conclusion, TAVI in patients with preexisting mitral prostheses-mechanical or biological-is feasible, safe, and effective and offers a valid alternative to conventional aortic valve replacement in this particular re-operation scenario. The JenaValve™ device does not interact with the mitral prosthesis and offers therefore due to its unique design a potential advantage.